Additive manufacturing technologies in the oral implant clinic: A review of current applications and progress - Huang, Shitou; Wei, Hongbo; Li, Dehua (Frontiers in Bioengineering and Biotechnology, 2023)
Additive manufacturing (AM) technologies can enable direct fabrication of customized physical objects with complex shapes, based on computer-aided design models. This technology is changing the digital manufacturing industry and has become a subject of considerable interest in digital implant dentistry. Personalized dentistry implant treatments for individual patients can be achieved through AM. Here, we review the applications of AM technologies in oral implantology, including implant surgery, and implant and restoration products, such as surgical guides for implantation, custom titanium meshes for bone augmentation, personalized or non-personalized dental implants, custom trays, implant casts, and implant-support frameworks, among others. This review also focuses on AM technologies commonly used in oral implantology. Stereolithography, digital light processing, and fused deposition modeling are often used to construct surgical guides and implant casts, while direct metal laser sintering, selective laser melting, and electron beam melting can be applied to fabricate dental implants, personalized titanium meshes, and denture frameworks. Moreover, AM technology also sometimes requires combination with milling and other cutting and finishing techniques, to ensure a product is suitable for its final application.